Potential transmission test of GP25 vaccine in normal flora bacteria of common carp culture media - Nuryati, Sri; Alimuddin, ,; Juliadiningtyas, Ayu Dhita (Jurnal Akuakultur Indonesia, 2015)
ABSTRACT Koi herpesvirus (KHV) is a virus that infects common carp and koi Cyprinus carpio. KHV attacks most stadia of common carp and koi and causes mortality up to 80–95% of the population. One way to prevent the spread of KHV is  by applying DNA vaccine. This research was conducted to test potential transmission of DNA vaccine encoding glycoprotein 25 (vaccine GP25) toward normal flora bacteria of media cultivation of common carp. Bacteria was isolated from pond water of common carp and tested for their sensitivity to ampicillin. Research was performed by adding vaccine GP25 to ampicillin-sensitive bacteria at a dose of 12.5 µg/100 µL and incubated at 28 °C for 30, 60, 180, and 300 minutes then plated on media containing ampicillin. The grown bacteria cells were tested for the existence of plasmid bearing gen GP25 through bacteria colony cracking. The results of this research showed that there was no bacteria contained plasmid bearing gen GP25. Keywords: DNA vaccines, common carp, vaccine safety  ABSTRAK Koi herpesvirus (KHV) merupakan virus yang menginfeksi ikan mas dan koi Cyprinus carpio. KHV menyerang hampir semua stadia ikan mas dan koi dan menyebabkan kematian hingga 80–95% dari populasi. Salah satu cara penanggulangan penyebaran KHV adalah dengan penggunaan vaksin DNA. Penelitian ini dilakukan untuk menguji potensi transmisi vaksin DNA glikoprotein 25 (vaksin GP25) pada bakteri flora normal pada media budidaya ikan mas. Bakteri diisolasi dari kolam budidaya ikan mas dan diuji sensitivitasnya terhadap antibiotik ampisilin. Penelitian dilakukan dengan menambahkan vaksin GP25 ke larutan bakteri sensitif ampisilin dengan dosis 12,5 µg/100 µL dan diinkubasi pada suhu 28 °C selama 30, 60, 180, dan 300 menit kemudian disebar pada media mengandung antibiotik ampisilin. Sel bakteri yang tumbuh diuji untuk mendeteksi keberadaan plasmid pembawa gen GP25 dengan menggunakan metode seleksi koloni bakteri (colony cracking). Hasil penelitian ini menunjukkan bahwa tidak ada bakteri yang mengandung plasmid pembawa gen GP25. Kata kunci: keamanan vaksin, ikan mas, vaksin DNA